(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This research work aimed at assessing the waste dump impacts on shallow groundwater physico-chemical and biological constituents of Suleja area. Groundwater samples were collected monthly at different locations within the study area. Forty-three (43) samples were collected during the dry season while forty-two (42) samples were collected for the wet season at the same samples locations for standard water quality laboratory analysis. The data sets obtained from the laboratory were subjected to descriptive statistics and Anova test to establish their relationship, including water quality index were calculated. The hydrochemical results revealed mean concentrations of physical parameters in the following order: Conductivity > TH > TDS > Alk > T > pH for the dry season while total dissolve solids range higher to that of total hardness concentrations during the wet season (Conductivity > TDS > TH > Alk > Temp. > pH). The minor ionic distributions revealed higher mean concentration of Sulphate ion followed by chloride, bicarbonate, carbon dioxide, and nitrate ions (SO4 > Cl- > HCO3 > CO2 > NO3) for the both seasons. The major ionic enrichment is in the following order: Ca2+ > Mg2+ > Na+ > K+) for the both seasons. The heavy metals ions revealed high mean concentration of iron followed by zinc, manganese, and copper during the dry season while concentration of manganese preceded that of zinc during the wet season. Both chemical oxygen demand and biological oxygen demand indicated similar concentrations trends through-out the seasons. Hydrochemical result depict average degree of temperature,...